2013
DOI: 10.1074/jbc.m113.487082
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of the Quinone-binding Site of the Complex II Homolog Quinol:Fumarate Reductase

Abstract: Background: Different quinone substrates are used by complex II. Results: Structural and kinetic analyses show that two arginine residues modulate the enzyme interaction with different quinones. Conclusion: Specific arginines compensate for each other in proton transfer during quinone oxidoreduction in the complex II homolog fumarate reductase. Significance: Plasticity in quinone binding may be important for bioenergetic transformations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
(74 reference statements)
0
7
0
Order By: Relevance
“…Kinetic measurements and docking studies of site specific mutations at the quinone binding site revealed that the ubiquinone and the menaquinone reduction does not take the same pathway for the proton transfer confirming that the site accommodates to the type of quinone used [55]. Importantly, not an individual residue functions as a partner for proton uptake; but several residues seem to be able to take this role.…”
Section: Accommodation Of Different Quinone Types In E Coli Complexesmentioning
confidence: 96%
See 1 more Smart Citation
“…Kinetic measurements and docking studies of site specific mutations at the quinone binding site revealed that the ubiquinone and the menaquinone reduction does not take the same pathway for the proton transfer confirming that the site accommodates to the type of quinone used [55]. Importantly, not an individual residue functions as a partner for proton uptake; but several residues seem to be able to take this role.…”
Section: Accommodation Of Different Quinone Types In E Coli Complexesmentioning
confidence: 96%
“…Importantly, not an individual residue functions as a partner for proton uptake; but several residues seem to be able to take this role. The flexibility of the quinone binding site was then suggested to be an evolutionarily conserved mechanism not only for maximizing, but also for regulating respiratory function [55].…”
Section: Accommodation Of Different Quinone Types In E Coli Complexesmentioning
confidence: 99%
“…It has been suggested that the quinone-binding pockets in these enzymes have a plastic structure, not a rigid structure as described by the so-called "lock and key" analogy. 31) Therefore, the NH-form of pyflubumide and the OHform of cyenopyrafen may share a common binding pocket but bind in different manners, as revealed for inhibitors that bind to the Q o site of complex III. 32) …”
Section: Comparison Of the Nh-form Of Pyflubumide With Anmentioning
confidence: 99%
“…Hence, only af ew high-resolution crystal structures of these complexes with bound quinones are available and the characterization of structural modifications occurring in the Qs ite during enzymet urnover remains challenging. [9] In this context, spectroscopict echniques such as electron paramagnetic resonance(EPR)and in particular hyperfine spectroscopies for example, electron nuclear double resonance (ENDOR), electron spin echo envelopem odulation (ESEEM) spectroscopy,a nd its two-dimensional variant hyperfine sublevel correlation (HYSCORE) spectroscopy are powerful in providing high-resolution structural data on SQ intermediates in bioenergetic complexes. [5,10,11] They allow the detection of magnetic nuclei (e.g.,n aturally abundant 1 Ha nd 14 N) located in the immediate vicinity of the radicals uch as those belongingt o the quinone itself, to the solvent, or to nearby amino acids.…”
mentioning
confidence: 99%